2022
DOI: 10.53730/ijhs.v6ns7.12110
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of cationic amphiphil conjugates with ciprofloxacin

Abstract: The aim: Design and synthesis of new compounds with antibacterial activity. Determination of the minimum inhibitory and minimum bactericidal concentration of conjugates of cationic amphiphiles based on quaternary salts of 1,4-diazabicyclo[2.2.2]octane with ciprofloxacin. Materials and methods: The article is dedicated to the synthesis and primary assessment of antibacterial activity in vitro of conjugates of cationic amphiphiles based on quaternary salts of 1,4-diazabicyclo[2.2.2]octane with ciprofloxacin agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…However, this conclusion emerges from theoretical calculations based on a simple summation of the known effects of hybrid components. Meanwhile, our previous study of hybrids of ciprofloxacin and tetracationic derivatives of DABCO showed the important role of the linker in determining the biological properties of the hybrid [ 11 ]. An analysis of publications shows that the mechanisms of hybrid molecules effect on bacterial cells have not been experimentally studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this conclusion emerges from theoretical calculations based on a simple summation of the known effects of hybrid components. Meanwhile, our previous study of hybrids of ciprofloxacin and tetracationic derivatives of DABCO showed the important role of the linker in determining the biological properties of the hybrid [ 11 ]. An analysis of publications shows that the mechanisms of hybrid molecules effect on bacterial cells have not been experimentally studied.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic ciprofloxacin hydrochloride (Zhejiang Guobang Pharmaceutical, Hangzhou, China) and two previously synthesized antibacterial compounds, DL 4 12 and hybrid DL 5 Cip6 ( Figure 1 ) were used. Synthesis and antimicrobial properties of DL 4 12 and DL 5 Cip6 were published earlier [ 6 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation